Universal and Specific Individual and Psychological Risk Factors for Traffic Accidents among Mentally Healthy People and People with Mental Disorders - Vasilchenko, A. (Psihologiâ i pravo, 2019)
The article presents the results of the research aimed to highlight the individual, psychological and cognitive risk factors of getting into a traffic accident depending on the presence of a mental disorder. 139 people aged from 18 to 59 years old (average age 30.44 years ± 9.56) were examined using a set of methods aimed at assessing the individual and typological features of self-control, individual, psychological and cognitive features of the driver's personality. Analysis of the results allowed identifying the universal individual and psychological risk factors for getting into a traffic accident. Specifically: systemic violations of self-regulation in the form of a violation of the connectedness of its stages, impulsiveness, risk-taking, physical aggression. When assessing the contribution of the parameter “guilty / not guilty in accident”, statistically significant differences in the indicators of cognitive methods were revealed. The convicted drivers were significantly distinguished by a high degree of workability, selectivity and accuracy of attention, providing a reactive response, with low processing speed of visual information and fatigue. Characteristics that significantly distinguish the convicted drivers, depending on the presence or absence of the factor “mental disorder”, were also highlighted. Mentally healthy drivers can be characterized by violations of the activation system, due to the orientation of the reward; low level of selectivity of attention, as well as high rates of dissociative driving style, which is characterized by disregard for the rules on the road; low level of planning and evaluation of the results of their own activities. Drivers with mental disorders were statistically significantly distinguished by high rates of risk-taking in the structure of self-control, low level of conscious planning, situational response conditions combined with suspiciousness, irritability, impulsiveness, and a decrease in criticality of mental activity. Characteristic features of their behavior on the road are high rates of anxious driving style, characterized by a heightened sense of alertness and tension while driving. Fatigue and difficulties in workability can be defined among the cognitive variables. В статье приводятся данные исследования индивидуально-психологических и когнитивных факторов риска попадания в дорожно-транспортное происшествие в зависимости от наличия фактора психическое расстройство. Было обследовано 139 человек в возрасте от 18 до 59 лет (средний возраст 30,44 года ± 9,56) комплексом методик, направленных на оценку индивидуально-типологических особенностей самоконтроля, индивидуально-психологических и когнитивных особенностей личности водителя. Анализ результатов позволил выделить универсальные индивидуально-психологические факторы риска попадания в дорожно-транспортное происшествие. Также были выделены характеристики, значимо отличающие водителей, виновных в ДТП, в зависимости от наличия или отсутствия фактора «психическое расстройство». Для водителей, принадлежащих к группе условной нормы характерны нарушения активационной системы, обусловленные ориентацией на награду; низкий уровень избирательности внимания, а также высокие показатели диссоциативного стиля вождения. Водителей с психическими расстройствами статистически значимо отличали высокие показатели поиска риска в структуре самоконтроля, низкий уровень осознанного планирования, ситуационная обусловленность реагирования в сочетании с подозрительностью, раздражительностью, импульсивностью и снижением критичности умственной деятельности.